Influence of fatigue in decision-making in football referees - Peralta-Geis, Mariona; Arboix-Alió, Jordi; Cabedo Sanromà, Josep; Mirabet Agulled, Raquel (SPORT TK-EuroAmerican Journal of Sport Sciences, 2021)
Objectives: The main objective of this study was to analyse the incidence of fatigue in decision-making in Catalan football’ referees. Secondary objectives were to assess the incidence of fatigue according to their category and years of experience. Methods: The sample was configured by 21 referees (17 men and 4 women) who solved 12 footballs’ game actions before running 2000m and 12 actions after this run. Results: Significant differences (p<0,05) were found in the successes rate before and after the physical effort both in faults and cards, less successes were shown with fatigue. Additionally, significant differences were observed between categories; higher category referees resolved better the game actions (faults and cards) than those with less category. Conclusions: It is important to keep in mind fatigue to analyse successes or errors in referee’s decisions. Likewise, to improve decision-making and physical condition in Catalan footballs’ referees is an aspect to keep working on.